2006
DOI: 10.1038/sj.bjc.6603181
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 Arg388 allele correlates with tumour thickness and FGFR4 protein expression with survival of melanoma patients

Abstract: A single nucleotide polymorphism in the gene for FGFR4 (ÀArg388) has been associated with progression in various types of human cancer. Although fibroblast growth factors (FGFs) belong to the most important growth factors in melanoma, expression of FGF receptor subtype 4 has not been investigated yet. In this study, the protein expression of this receptor was analysed in 137 melanoma tissues of different progression stages by immunohistochemistry. FGFR4 protein was expressed in 45% of the specimens and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 41 publications
5
54
1
Order By: Relevance
“…We also found that the patients with the Gly/Gly genotype were associated with a greater risk of recurrence, but were not associated with metastasis compared with Arg allele carriers. Our results are in accordance with a study of melanoma patients, which showed no correlation between the FGFR4 genotype and metastasis (Streit et al, 2006). One possible reason for positive result in recurrence could possibly be due to false positives based on a relatively small number of recurrence cases (less than 10%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that the patients with the Gly/Gly genotype were associated with a greater risk of recurrence, but were not associated with metastasis compared with Arg allele carriers. Our results are in accordance with a study of melanoma patients, which showed no correlation between the FGFR4 genotype and metastasis (Streit et al, 2006). One possible reason for positive result in recurrence could possibly be due to false positives based on a relatively small number of recurrence cases (less than 10%).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in subsequent larger studies of melanoma, breast, and colon cancer, no obvious association between the Gly388Arg genotype and cancer prognosis was found (Becker et al, 2003;Jezequel et al, 2004;Spinola et al, 2005b;Streit et al, 2006).…”
mentioning
confidence: 99%
“…Some reports show that FGFR4 G388R is associated with poor prognosis in several malignancies such as lung, skin, head and neck, colon, breast, and prostate cancer (151)(152)(153)(154)(155). Others, however, find no correlation between FGFR4 G388R and poor prognosis (156)(157)(158)(159).…”
Section: Impaired Termination Of Fgfr Signalingmentioning
confidence: 93%
“…Moreover, the analysis of 137 melanoma tissues by immunohistochemistry showed that 45% of the specimens expressed FGFR4 at different levels and correlated with pTNM tumour stages, metastases, number of primary tumors and survival (Streit et al, 2006). In another independent study with 218 samples from melanoma, 285 squamous cell carcinoma, 300 basal cell carcinoma and 870 controls, it was observed no association between the presence of the SNP and predisposition to develop skin cancer.…”
Section: Melanomamentioning
confidence: 95%